The Effect of Work Atmosphere, Training, Incentives, and Motivation on Sales Productivity in PT. Suzuki Indonesia - Sigit Setiawan; Bedjo Sujanto; Dedi Purwana (Program Studi S3 Ilmu Manajemen, 2019)
The aims of this study effect of work atmosphere, training, incentives, and motivation on sales force productivity at PT. Suzuki Indonesia. This study uses correlational studies. The sample from this study was 120 people selling PT. Suzuki Indonesia personnel in the Jabodetabek area. The results of this study indicate that; 1) The work environment has a positive direct effect on the productivity of the sales force of 0.613 with a tcount of 8.43, 2) training has a positive direct effect on sales force productivity of 0.628 with a tcount of 8.77, 3) incentives have a positive direct effect on labor productivity sales of 0.609 with a tcount of 8.34, 4) motivation has a positive direct effect on sales force productivity of 0.635 with a tcount of 8.94, 5) work environment, training, incentives, and motivation together have a positive direct effect on productivity sales force of 0.812 with a tcount of 55.78. Thus an increase in sales force productivity can be achieved well if there is a strong influence of the work environment, training, incentives and motivation that are well-developed.